2000
DOI: 10.2135/cropsci2000.4051350x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Wear Tolerance in Seashore Paspalum and Bermudagrass

Abstract: tween species. Warm-season turfgrass is typically more wear tolerant than cool-season turf (Youngner, 1961; Traffic causes shoot injury to turfgrass, with resulting inhibition Beard, 1973). Cultural practices, such as increased mowof growth and reduction of quality. Turfgrasses in high traffic venues are generally selected for tolerance to traffic or for an ability to ing height (Beard, 1973; Youngner, 1961), moderate N quickly outgrow the injury. However, limited knowledge exists on fertilization levels (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 18 publications
6
84
3
Order By: Relevance
“…Vincent (1991) confirmed that the strength of the leaves is linearly related to the amount of sclerenchyma and lignin, because lignified fibres from a range of grasses had identical mechanical properties. These investigations suggested that wear tolerance corresponds with anatomical and morphological plant characteristics, namely total cell wall content, quantity of sclerenchyma fibres, tiller density, tiller dry weight, leaf width, leaf tensile strength and shoot density (Hoffman et al, 2010;Shearman and Beard, 1975a,b;Trenholm et al, 2000). This relationship was also confirmed by Dowgiewicz et al (2011) for Agrostis sp.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Vincent (1991) confirmed that the strength of the leaves is linearly related to the amount of sclerenchyma and lignin, because lignified fibres from a range of grasses had identical mechanical properties. These investigations suggested that wear tolerance corresponds with anatomical and morphological plant characteristics, namely total cell wall content, quantity of sclerenchyma fibres, tiller density, tiller dry weight, leaf width, leaf tensile strength and shoot density (Hoffman et al, 2010;Shearman and Beard, 1975a,b;Trenholm et al, 2000). This relationship was also confirmed by Dowgiewicz et al (2011) for Agrostis sp.…”
Section: Introductionmentioning
confidence: 68%
“…The quantitative data are generally more accurate than the subjective data, but the time and costs associated with collecting this information limits its use. The most often used quantitative method is individual plant counts within the collected plug (Trenholm et al, 2000;Vanini et al, 2007). In recent years, digital image analysis has been more frequently and effectively used to measure turfgrass cover.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that stolon morphological traits of bermudagrass are genetically controlled (de Kroon et al, 1994), and their infl uence on turfgrass quality and cold tolerance have been widely studied (Dudeck and Murdoch, 1998;Roche and Loch, 2005;Hensler et al, 1998;Anderson et al, 2007). High stolon density is of crucial importance for cold hardiness and spring recovery from winter injury in many warm-season species (Hensler et al, 1998;Trenholm et al, 2000;Anderson et al, 2007;Rimi et al, 2013b). Cultivar selection of bermudagrass, especially in the transition zone, takes into account stolon density since it has been well correlated to cold hardiness (Rimi et al, 2013b;Dunn and Diesberg, 2004).…”
mentioning
confidence: 99%